2021
DOI: 10.1002/ange.202015639
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations suggest Vitamins, Retinoids and Steroids as Ligands of the Free Fatty Acid Pocket of the SARS‐CoV‐2 Spike Protein**

Abstract: We investigate binding of linoleate and other potential ligands to the recently discovered fatty acid binding site in the SARS‐CoV‐2 spike protein, using docking and molecular dynamics simulations. Simulations suggest that linoleate and dexamethasone stabilize the locked spike conformation, thus reducing the opportunity for ACE2 interaction. In contrast, cholesterol may expose the receptor‐binding domain by destabilizing the closed structure, preferentially binding to a different site in the hinge region of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Rational drug design approaches have been directed toward the LA pocket with the aim of stabilizing receptor binding-incompetent closed conformations (Ellis et al, 2021; -S3. Shoemark et al, 2021). It appears that the LA pocket also has long-range effects on allosteric networks that include neighboring chains, NTD, and distant S1/S2 cleavage sites (Oliveira et al, 2022;Tan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Rational drug design approaches have been directed toward the LA pocket with the aim of stabilizing receptor binding-incompetent closed conformations (Ellis et al, 2021; -S3. Shoemark et al, 2021). It appears that the LA pocket also has long-range effects on allosteric networks that include neighboring chains, NTD, and distant S1/S2 cleavage sites (Oliveira et al, 2022;Tan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Another hormone in Table 1 is calcitriol (1,25-dihydroxycholecalciferol vitamin D), a steroid hormone that binds to and activates the vitamin D receptor in the nucleus of the cell, regulating multiple genes. Other groups have identified calcitriol and other steroids as ligands for the S protein FABP [ 6 , 32 ]. Unlike other steroids, calcitriol interacts with Arg408 and Gln409 on S, which increases its binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…It also had an EC 50 value of 9.6 µM in Vero E6 cells, which was attributed to binding to the spike RBD [ 37 ]. Shoemark and colleagues also reported Vitamin K2 as a best binder, and adapalene and vitamin A as a tight binders to the FABP [ 6 ]. Figure 4 shows a superimposition of linoleic acid with adapalene in the spike FABP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two forms of spike trimer have been reported in previous studies: open (Apo) and Locked S conformer. Recent findings indicated that switching Apo to Locked form could significantly reduce the spike protein affinity to ACE2 though the interaction of ligands to fatty acid binding pocket (FAB) of spike trimer 34,35 . Protease is an essential enzyme present in viruses 36 .…”
mentioning
confidence: 99%